A Transcription Factor-Based Biosensor for Detection of Itaconic Acid - Hanko, Erik K. R. (ACS Synth Biol, 2018)
[Image: see text] Itaconic acid is an important platform chemical that can easily be incorporated into polymers and has the potential to replace petrochemical-based acrylic or methacrylic acid. A number of microorganisms have been developed for the biosynthesis of itaconate including Aspergillus terreus, Escherichia coli, and Saccharomyces cerevisiae. However, the number of strains and conditions that can be tested for increased itaconate titers are currently limited because of the lack of high-throughput screening methods. Here we identified itaconate-inducible promoters and their corresponding LysR-type transcriptional regulators from Yersinia pseudotuberculosis and Pseudomonas aeruginosa. We show that the YpItcR/P(ccl) inducible system is highly inducible by itaconic acid in the model gammaproteobacterium E. coli and the betaproteobacterium Cupriavidus necator (215- and 105-fold, respectively). The kinetics and dynamics of the YpItcR/P(ccl) inducible system are investigated, and we demonstrate, that in addition to itaconate, the genetically encoded biosensor is capable of detecting mesaconate, cis-, and trans-aconitate in a dose-dependent manner. Moreover, the fluorescence-based biosensor is applied in E. coli to identify the optimum expression level of cadA, the product of which catalyzes the conversion of cis-aconitate into itaconate. The fluorescence output is shown to correlate well with itaconate concentrations quantified using high-performance liquid chromatography coupled with ultraviolet spectroscopy. This work highlights the potential of the YpItcR/P(ccl) inducible system to be applied as a biosensor for high-throughput microbial strain development to facilitate improved itaconate biosynthesis.